2015
DOI: 10.1038/srep16016
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic patterns of diversification dynamics following the colonization of Melanesian islands

Abstract: The fate of newly settled dispersers on freshly colonized oceanic islands is a central theme of island biogeography. The emergence of increasingly sophisticated methods of macroevolutionary pattern inference paves the way for a deeper understanding of the mechanisms governing these diversification patterns on lineages following their colonization of oceanic islands. Here we infer a comprehensive molecular phylogeny for Melanesian Exocelina diving beetles. Recent methods in historical biogeography and diversifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 54 publications
6
45
0
Order By: Relevance
“…Following the habitat constraints hypotheses (Ribera, ), one can predict that New Guinean lotic lineages should exhibit high levels of local endemism and population structure between watersheds and geological terranes on the island because of low dispersal in stable environments. Such a pattern has been previously suggested by several studies involving large time‐calibrated molecular phylogenies, including lotic Exocelina diving beetles (Toussaint, Hendrich, Shaverdo, & Balke, ; Toussaint et al., ), rainbowfishes (Unmack et al., ) and the New Guinea snapping turtle Elseya novaeguineae (Georges et al., ). However, there are no studies to date that focus on fine‐scale phylogeographic patterns among populations of aquatic lineages across the island (but see Lam et al., ; Georges et al., for Miocenic divergence of regional populations).…”
Section: Discussionsupporting
confidence: 58%
“…Following the habitat constraints hypotheses (Ribera, ), one can predict that New Guinean lotic lineages should exhibit high levels of local endemism and population structure between watersheds and geological terranes on the island because of low dispersal in stable environments. Such a pattern has been previously suggested by several studies involving large time‐calibrated molecular phylogenies, including lotic Exocelina diving beetles (Toussaint, Hendrich, Shaverdo, & Balke, ; Toussaint et al., ), rainbowfishes (Unmack et al., ) and the New Guinea snapping turtle Elseya novaeguineae (Georges et al., ). However, there are no studies to date that focus on fine‐scale phylogeographic patterns among populations of aquatic lineages across the island (but see Lam et al., ; Georges et al., for Miocenic divergence of regional populations).…”
Section: Discussionsupporting
confidence: 58%
“…In clade CVI, New Guinea was colonized out‐of‐Australia, in the mid‐Miocene, which agrees with the proposed onset of more significant formation of land and altitude in the region of present day New Guinea (Hall ,, , synopsis in Toussaint et al ). Toussaint et al (, ) also found a similar pattern in Exocelina diving beetles (Copelatinae) suggesting this was a time when large‐scale environmental change initiated major clade formation and species‐level diversification in New Guinea.…”
Section: Discussionmentioning
confidence: 78%
“…More sophisticated phylogenetic methods and molecular clock divergence time estimation have greatly improved our understanding of the biogeography of several taxa (Lohman et al ., ; de Bruyn et al ., ). In particular, the study of evolutionary patterns and processes in insect clades of the IAA has recently experienced remarkable progress (Braby & Pierce, ; Balke et al ., ; Müller & Beheregaray, ; Müller et al ., , ; Condamine et al ., , ; Toussaint et al ., , , ,c,d; Tänzler et al ., , ; Clouse et al ., ). Most of the clades studied are widespread in the IAA and therefore provide a window into the impact of geological and climatic factors on lineage diversification.…”
Section: Introductionmentioning
confidence: 99%